2018
DOI: 10.1016/j.nbd.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Newfound effect of N-acetylaspartate in preventing and reversing aggregation of amyloid-beta in vitro

Abstract: Although N-acetylaspartate (NAA) has long been recognized as the most abundant amino acid in neurons by far, its primary role has remained a mystery. Based on its unique tertiary structure, we explored the potential of NAA to modulate aggregation of amyloid-beta (Aβ) peptide 1-42 via multiple corroborating aggregation assays along with electron microscopy. Thioflavin-T fluorescence assay demonstrated that at physiological concentrations, NAA substantially inhibited the initiation of Aβ fibril formation. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Levels of tNAA have been shown to be highly heritable (Batouli et al, ), but are also sensitive to early environmental influences, including stress (McLean et al, ). Future large scale studies of genetic and environmental influences on PCu/PCC metabolite levels in humans across the lifespan will be required to address this critical question, which may have implications for understanding lifespan influences on cognitive and neural ageing (Dollé et al, ; Jagust & Mormino, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of tNAA have been shown to be highly heritable (Batouli et al, ), but are also sensitive to early environmental influences, including stress (McLean et al, ). Future large scale studies of genetic and environmental influences on PCu/PCC metabolite levels in humans across the lifespan will be required to address this critical question, which may have implications for understanding lifespan influences on cognitive and neural ageing (Dollé et al, ; Jagust & Mormino, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggest some regional specificity of the link between BOLD and tNAA, since we found no correlation between OCC tNAA and the OCC response to scenes. This could reflect some unique physiological properties of PCu/PCC and/or tNAA (Dollé et al, ). NAA is not distributed homogeneously in the brain, but rather, levels are highly variable among different neuronal types (Moffet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…NAA is transported to glial cells, particularly oligodendrocytes, where it is likely used for lipid and myelin synthesis (Burri, Steffen, & Herschkowitz, ; Chakraborty, Mekala, Yahya, Wu, & Ledeen, ; Francis et al, ; Moffett, Ross, Arun, Madhavarao, & Namboodiri, ), although an absence of NAA does not preclude myelin formation (Martin, Capone, Schneider, Hennig, & Thiel, ). NAA is also potentially involved in osmoregulation (Baslow, ), nitrogen balance (Moffett et al, ), and the inhibition of protein aggregation (Dolle et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that in the presence of NAA, Aβ or alphasynuclein aggregation should be prevented. In support, it has been reported that NAA suppresses the aggregation of Aβ42 (Dollé et al, 2018). Thus, it appears that increase in the Aβ or alpha synuclein aggregation under the pathologic conditions, is due to decrease in the NAA concentration making it insufficient to modulate aggregation pathway.…”
Section: Discussionmentioning
confidence: 76%